The influence of compensation, school climate and principal transformational leadership on job satisfaction in higher vocational colleges at Wuxi City, China - Li, Shao; Sahimi, Nurul Nadiah Binti (Edelweiss Applied Science and Technology, 2025)
The objective of this study was to investigate the impact of compensation, school climate, and principal transformational leadership on teachers' job satisfaction in Wuxi public higher vocational colleges. Data were gathered via a structured questionnaire survey, and SPSS and AMOS software were employed for quantitative analysis. A comprehensive questionnaire encompassing compensation, school climate, principal transformational leadership, and teachers' job satisfaction was developed to survey teachers at public vocational colleges in Wuxi City. To ensure data quality, reliability and validity tests were conducted, and pre-processed data underwent thorough cleaning. Utilizing structural equation modeling (SEM) analysis, the direct effects of each factor on job satisfaction were thoroughly examined. The findings indicate that compensation, school climate, and principal transformational leadership significantly and positively influence the job satisfaction of teachers in Wuxi public higher vocational colleges. This study elucidates the critical mechanisms affecting teachers' job satisfaction, underscores the pivotal role of compensation, school climate, and principal transformational leadership in enhancing teachers’ job satisfaction, and provides valuable insights for college managers and policymakers aiming to improve teachers’ job satisfaction and well-being. Additionally, it establishes a robust theoretical and empirical foundation for future research in this area.